GOOD CORPORATE GOVERNANCE PADA BADAN USAHA MILIK NEGARA: STUDI SYSTEMATIC LITERATURE REVIEWGOOD CORPORATE GOVERNANCE PADA BADAN USAHA MILIK NEGARA: STUDI SYSTEMATIC LITERATURE REVIEW - Saproni (Jurnal Acitya Ardana, 2025)
Good Corporate Governance (GCG) is essential for State-Owned Enterprises (SOEs) to fulfill their crucial role in Indonesia's economy. This study aims to map the existing research on the impact of GCG on SOEs using a systematic literature review (SLR) method. The PRISMA framework was utilized for the selection of literature to mitigate bias. The Google Scholar database was used as the search engine, supported by the Publish or Perish software. Based on predetermined inclusion and exclusion criteria, this study selected 24 scientific articles published between 2015 and 2025 for review. The results show significant development in research from year to year, as well as considerable diversity among previous studies. Agency theory was the most predominantly used theoretical foundation. The board of commissioners and committees were the most popular GCG indicators. With multiple linear regression being the most frequently used analysis technique, prior research has produced varied and often inconsistent findings. With these findings, this study is expected to serve as a comprehensive guide for future research on the topic of GCG in SOEs.